2016
DOI: 10.1016/j.scitotenv.2015.12.145
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reliability of uptake and elimination kinetics modelling approaches for estimating bioconcentration factors in the freshwater invertebrate, Gammarus pulex

Abstract: This study considers whether the current standard toxicokinetic methods are an accurate and applicable assessment of xenobiotic exposure in an aquatic freshwater invertebrate. An in vivo exposure examined the uptake and elimination kinetics for eight pharmaceutical compounds in the amphipod crustacean, Gammarus pulex by measuring their concentrations in both biological material and in the exposure medium over a 96 h period. Selected pharmaceuticals included two anti-inflammatories (diclofenac and ibuprofen), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 37 publications
4
45
0
Order By: Relevance
“…Again, k 1 was observed to decrease over time. These decreases again are potentially the cause of the lack-of-fits, as suggested previously (Miller et al., 2016). The reason for the decrease in k 1 over time could be attributed to either sorption on to the cuticle of the animal during the uptake phase, toxicodynamic effects where the pharmaceuticals are reducing the ability of the organism to eliminate the compound or growth dilution of the animal.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Again, k 1 was observed to decrease over time. These decreases again are potentially the cause of the lack-of-fits, as suggested previously (Miller et al., 2016). The reason for the decrease in k 1 over time could be attributed to either sorption on to the cuticle of the animal during the uptake phase, toxicodynamic effects where the pharmaceuticals are reducing the ability of the organism to eliminate the compound or growth dilution of the animal.…”
Section: Resultssupporting
confidence: 72%
“…The reason for the decrease in k 1 over time could be attributed to either sorption on to the cuticle of the animal during the uptake phase, toxicodynamic effects where the pharmaceuticals are reducing the ability of the organism to eliminate the compound or growth dilution of the animal. However, preliminary evidence in (Miller et al., 2016) and the larger decreases in k 1 at the earlier time interval (this study) suggest that sorption might be a significant cause of the decreases in k 1 over time. In the cases of warfarin, carbamazepine, diazepam and temazepam an apparent plateau had been reached indicating k 1 constancy and it was possible to use this value to estimate the BCF parent .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Azoles potentially adsorbed to the exoskeleton of gammarids can influence the determination of BAFs by overestimating internal concentrations and uptake rates. Miller et al (2016) 65 analyzed the exoskeletons of gammarids that molted during the exposure period. They observed that the percentage of the adsorbed fraction on the total chemical mass in the animal was between 3 and 24% for five out of eight pharmaceuticals studied.…”
Section: Environmental Science and Technologymentioning
confidence: 99%